Nationalism and the issue of Kurdish identity It is a theoretical analysis - Aziz, Prof.Dr. Maher Abdel Wahed; Hama, Dr.Yasin Salih (Sulaimani Journal for Humanities, 2025)
In this paper the interpretation and analysis of nationalism from the perspective of history and political sociology is discussed and attempts are made to answer several questions such as: What is nationalism and what is its relationship to the Kurdish question? What are the main schools in this field? Is it possible to have a different identity in the Federal State? What are the challenges and obstacles of national identity in the Kurdistan Region? Based on the theoretical analysis of political literature in the field of nationalism and from contemporary thinkers and theorist’s viewpoints such as Ernest Gellner, Anthony D. Smith and Benedict Anderson. The paper has found that it is possible to have dual identities in a federal state, but the issue of identity in Kurdistan is facing major challenges.